Nomina Makian Dalam Film Jakarta Vs Everybody - Marhaji Aidil Adha; Agustina (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to (1) Reveal and describe the form of swear nouns in the film Jakarta Vs Everybody. (2) Reveal and describe the types of swear nouns in the film Jakarta Vs Everybody. (3) Reveal and describe the function of the curse noun in the film Jakarta Vs Everybody. This research uses qualitative methods using descriptive methods. The results of this study are, First, based on the results of the study, a total of 51 data were found included in the swear noun, in this study the approximately word-shaped swear noun amounted to 34 data. Second. Based on the type in this study, 6 types of swear nouns ((a), conditions, (b) animals, (c) objects, (d) body parts, (e) kinship, (f) profession) and 1 type of swear noun ((g) Subtle creatures) were found, from several types of swear nouns that dominate, namely the type of animal swear noun totaling 17 data. Third, based on the function of using swear expressions found there are 4 functions of swearing, namely (1) When swearing is used as a habit or group rule, (2) Curses are used intentionally to insult, revile, threaten, surprise, and hurt or disturb Foul or indecent language is used as a joke or intended to joke (4) Curses used to express strong emotions, such as surprise, or when something occurs, in this study the most dominating is dirty or indecent language used as a joke or intended to joke which amounts to 19 data.